Association between electronic cigarette use and depression among Thai adolescents: The Thailand National Health Examination Survey 2019-2020 - Patanavanich R. (2023)
INTRODUCTION Depression and e-cigarette use among adolescents are two health burdens. However, the association between these dual problems have been less studied, especially in low- and middle-income countries. This study examined the association between depression and e-cigarette use among adolescents in Thailand. METHODS This cross-sectional study used the sub-sample of the sixth Thai National Health Examination Survey conducted between 2019 and 2020. A total of 4237 adolescents aged 10-19 years were included. Self-reported depression was captured using the 20-item Centre for Epidemiologic Studies Depression Scale (CES-D). We applied a complex survey multiple logistic regression to assess whether e-cigarette use was associated with depression. RESULTS The mean age of the participants was 14.6 years, 5.3% were ever e-cigarette users, and 2.9% were current e-cigarette users. 37.8% of the participants were categorized at risk for depression. Among e-cigarette users, 51.6% of ever e-cigarette users and 52.9% of current e-cigarette users were at risk for depression. Multiple logistic regression revealed that ever e-cigarette users were at higher risk for depression (AOR=1.66; 95% CI: 1.02-2.71; p=0.042) than never e-cigarette users. Current e-cigarette was not associated with a higher risk for depression (AOR=1.37; 95% CI: 0.77-2.45; p=0.263). CONCLUSIONS E-cigarette use and depression among adolescents are global public health concerns. There is also a need for effective screening, prevention, and intervention to reduce adverse outcomes of e-cigarette use and depression. In addition, the government should strengthen current policies and close legal loopholes to prevent the tobacco industry tactics and keep e-cigarettes away from adolescents.